2020
DOI: 10.3390/ijms21093236
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ERK-Hippo Interplay in Cancer Therapy

Abstract: Extracellular signal-regulated kinase (ERK) is a part of the mitogen-activated protein kinase (MAPK) signaling pathway which allows the transduction of various cellular signals to final effectors and regulation of elementary cellular processes. Deregulation of the MAPK signaling occurs under many pathological conditions including neurodegenerative disorders, metabolic syndromes and cancers. Targeted inhibition of individual kinases of the MAPK signaling pathway using synthetic compounds represents a promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 134 publications
0
18
0
Order By: Relevance
“…On the other hand, active MAPK signaling also turns on some negative feedback loops, which help cells return to quiescent status [56][57][58]. An aberrant activation of MAPK signaling frequently induces human cancers or developmental disorders, though an extremely high MAPK signaling may induce cell death or senescence under some conditions [59][60][61][62][63].…”
Section: Hyperactive Ras/raf/mek/erk (Mapk) Signaling In Cancersmentioning
confidence: 99%
“…On the other hand, active MAPK signaling also turns on some negative feedback loops, which help cells return to quiescent status [56][57][58]. An aberrant activation of MAPK signaling frequently induces human cancers or developmental disorders, though an extremely high MAPK signaling may induce cell death or senescence under some conditions [59][60][61][62][63].…”
Section: Hyperactive Ras/raf/mek/erk (Mapk) Signaling In Cancersmentioning
confidence: 99%
“…Multiple studies have suggested a molecular cross-talk between MAPK and Hippo signaling cascades during tumor development. 25 However, the specific biochemical interplay between Yap and MAPK pathways during hepatocarcinogenesis has not been characterized satisfactorily. It would be of high importance to determine the molecular mechanisms whereby YAP, but not TAZ, modulates p-ERK activity in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…2A). HIPPO interferes with the RAS and PI3K pathways that control cell death induction [111], acting as a tumor suppressor pathway [112]. Through cross-inhibition, MST and AKT differentially regulate the expression level of pro-apoptotic effectors (NOXA, FASL, BIM, TRAIL).…”
Section: An Altered Hippo Pathway Induces Aerobic Glycolysis In Stsmentioning
confidence: 99%